Engineering Surveys along the Trans-Alaska Pipeline. - Godfrey,Randy N; Eaton,Robert A (1986)
The three-year research project had two general objectives: 1) to systematically obtain data on selected highway, airfield and pipeline workpad test sites and adjacent terrain to establish the rates and types of modifications in permafrost-dominated regions, and 2) to provide the basis for improved design critieria and specifications governing road, airfield and workpad construction and restoration in permafrost zones that are influenced by many different seasonal climatic requires. This report presents the results of 14 test areas not covered in CRREL Report 80-19, Environmental Engineering and Ecological Baseline Investigations along the Yukon River-Prudhoe Bay Haul Road(Brown and Berg 1980). The data presented here will be utilized for improving road, workpad and airfield design and construction, and for developing methods of minimizing the impacts on the environment in Alaska. The results show that thaw depths adjacent to the test sites increased each year from 1976 to 1978, causing continued settlement along the embankments. The depths of thaw beneath the gravel surface road sideslopes has caused the trafficked surface to become narrower as the sideslopes become wider and flatter. Since the rate of permafrost degradation and resulting thaw settlement has decreased annually, the thermal regime appears to be stabilizing. When the gravel workpads, roadways and runways are graded, any edge berms that would inhibit lateral runoff of water must be removed. Runoff water that ponds on the tundra adjacent to the roadway or workpad or airfield embankments should be avoided to eliminate subsidence caused by heat absorption.